2020
DOI: 10.1001/jamapsychiatry.2019.3561
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validity ofDSM-5Attenuated Psychosis Syndrome

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
54
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 110 publications
2
54
2
Order By: Relevance
“…When psychotic-like experiences persist and are associated with distress or impairment, they are thought to represent a meaningful diagnostic entity known as the "clinical high-risk for psychosis (CHR) syndrome," sometimes referred to as "attenuated" or "prodromal" psychosis 19 . Even though the CHR syndrome progresses to frank SCZ in just one-fourth of cases within 36 months of its identification 20 , CHR youth who do not progress continue to have pronounced social and cognitive impairment 21 and may benefit from specialized attention.…”
Section: Introductionmentioning
confidence: 99%
“…When psychotic-like experiences persist and are associated with distress or impairment, they are thought to represent a meaningful diagnostic entity known as the "clinical high-risk for psychosis (CHR) syndrome," sometimes referred to as "attenuated" or "prodromal" psychosis 19 . Even though the CHR syndrome progresses to frank SCZ in just one-fourth of cases within 36 months of its identification 20 , CHR youth who do not progress continue to have pronounced social and cognitive impairment 21 and may benefit from specialized attention.…”
Section: Introductionmentioning
confidence: 99%
“…In the SIPS, the characterization used is Attenuated Positive Symptoms Syndrome (APSS). Seven years ago, the DSM-5 introduced the Attenuated Psychosis Syndrome (APS) diagnosis in the research appendix, listed in both section II and section III (21) (Figure 1). This diagnosis is defined by the presence of delusions, hallucinations, or disorganized speech in attenuated form, but with sufficient severity and frequency to warrant clinical attention (23,24) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This diagnosis is defined by the presence of delusions, hallucinations, or disorganized speech in attenuated form, but with sufficient severity and frequency to warrant clinical attention (23,24) (Figure 1). The diagnostic, prognostic, and therapeutic characteristics of this diagnosis have been recently appraised by a systematic review and meta-analysis (21). This review concluded that DSM-5-APS criteria have received substantial concurrent and prognostic validation, mostly driven by research in adult populations (21).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations